Extent of Teachers’ Participation in In-Service Training Programmes for Secondary Schools Effectiveness in Anambra State - Obineme, Patience Obiageli; Umeozor, Juliana; Chime, Gladys Ozululuonye (International Journal of Educational Management, 2021)
The inefficiency of many secondary school teachers’ whose defects have continued to cause poor performances of their task for school effectiveness in Anambra State has necessitated this study. The study examined the extent of teachers’ participation in in-service training programmes for secondary schools effectiveness in Anambra State. Two research questions guided this study. The study adopted the descriptive survey research design. Population for the study consisted of 5,800 teachers from the 259 public secondary schools located within 6 education zones in Anambra State. Sample size of the study comprised 580 teachers from 26 public secondary schools, selected out of the entire teachers’ population at 10% (percent) using stratified random sampling technique. A 24-item questionnaire titled: “Extent of Teachers’ Participation in In-Service Training Programmes for Secondary Schools Effectiveness Questionnaire (ETPISTPSSEQ)” developed by the researchers was the main instrument for data collection. The research instrument was validated by three experts. A pilot-test was carried out in Delta State in order to determine the reliability of the questionnaire. Data collated were analyzed using mean scores and standard deviation. The findings of the study revealed that the extent to which teachers’ participated in on-the-job and off-the-job in-service training programmes for secondary schools effectiveness in Anambra State, were to a low extent. Among the recommendations which were proffered from the findings of the study are that the Anambra State Government should promote teachers participation in in-service training programmes through adequate financing, scholarship, and policy implementation.